Uric acid levels and their relation to incapacities in acute cerebrovascular disease - Julio López Argüelles; Joan Rojas Fuentes; Ricardo Verdecia Fraga (Medisur)
Background: cerebrovascular disease and ischemic cardiopathy can be considered as an epidemic and constitute the first cause of incapacities in developed countries. Multiple studies have shown the association between uric acid levels and cerebrovascular diseases. Objective: To correlate the levels of serum uric acid and incapacities in the acute phase of cerebrovascular disease. Methods: A correlational study was carried out with 217 patients with acute cerebrovascular disease. The patient’s incapacity level was measured by using the Barthel Index and those results were related with the serum uric acid levels and other variables. Results: Male patients have higher levels of uric acid (p=0, 04; r=0, 13). Age and Barthel index were p < 0,001; r = -0, 30 and uric acid levels and Barthel Index were p=0, 03; r=-0, 14. The principal predicting factors of incapacity in the acute phase of cerebrovascular disease were the high levels of uric acid, age and diabetes mellitus. Conclusions: It is shown that the highest is the level of uric acid at advanced age; the greatest is the risk of suffering from incapacity in acute phases of cerebrovascular diseases.